The Kingfisher first picture atlas - Chancellor, Deborah; Lewis, Anthony (London : Kingfisher, 2007)
Explains how to use an atlas and presents maps of and describes seventeen regions around the world, as well as the oceans.
Includes index.
Originally published in 2005.
Horn Book
Library Media Connection
3.2
K-3.
Keywords: Children's atlases; Atlases; Atlases